Reliability analysis of a newly developed detector for monitoring spine health. (November 2017) - Li, Ting; Su, Yu; Wu, Lanhui; Pan, Boan; Li, Yan
Abstract: Following with tons of people studying and working in a sitting posture for long, spine disease became one of the most important occupational health problems. The patients with condition worsen have to suffer harmful CT scans or even painful serial lumbar puncture. We innovatively developed a biomedical optics based detector for spine health monitoring and particularly improved the circuit design for feeble signal detection. A series of experiments were performed to fully test its reliabilities, including scalability, noise and crosstalk, sensitivity, stability etc. The results showed that this device was very reliable, sensitive, and stabile, suggested the promising clinical use of our novel device in spine/spinal marrow health monitoring and diagnosis. Highlights: Innovatively developed a biomedical optics based detector for spine health monitoring Improved the circuit design for feeble signal detection Fully test the reliabilities, including scalability, noise and crosstalk, sensitivity of the novel device